ANTICANCER ACTIVITY OF CALANONE ON HeLa CELL LINE - Heny Ekowati; Indwiani Astuti; Mustofa Mustofa (Universitas Gadjah Mada, 2010)
Calanone (coumarin derivate compound), isolated from Calophyllum sp. had been shown to have cytotoxic activity on leukemia L1210 cell line with IC50 = 59.40 mg/mL. Calanone presumed have anticancer activity on HeLa cervical carcinoma cell. This study was conducted to investigate the cytotoxic and apoptotic activity of calanone and its effect to p53 and p21 expression on HeLa cervical carcinoma cell. Cytotoxic assay of calanone was performed on HeLa cell line, using MTT assay. Apoptotic assay was performed on HeLa cell line incubated with calanone for 24 h, by immunofluororescence method, using fluorochromes ethidium bromide and acridine orange. Expression of p53 was examined on HeLa cell line, by PCR with p53 wild-type primer. Expression of p21 was examined on HeLa cell line, by immunohistochemistry method. 5-fluorourasil was used as positive control in cytotoxic, apoptotic assay, and p53 expression. The result showed that calanone has cytotoxic activity on HeLa cell line, with IC50 = 22.887 mg/mL, caused cytotoxicity through apoptotic mechanism, increase p53 tumor suppressor gene expression, while the p21 expression test showed a negative result.